Impact of SARS-CoV-2 vaccination on systemic immune responses in people living with HIV - Bessen, Clara; Plaza-Sirvent, Carlos; Simsek, Agit; Bhat, Jaydeep; Marheinecke, Corinna; Urlaub, Doris; Bonowitz, Petra; Busse, Sandra; Schumann, Sabrina; Blanco, Elena Vidal; Skaletz-Rorowski, Adriane; Brockmeyer, Norbert H.; et al. (Frontiers in Immunology, 2022)
Despite the development of vaccines, which protect healthy people from severe and life-threatening Covid-19, the immunological responses of people with secondary immunodeficiencies to these vaccines remain incompletely understood. Here, we investigated the humoral and cellular immune responses elicited by mRNA-based SARS-CoV-2 vaccines in a cohort of people living with HIV (PLWH) receiving anti-retroviral therapy. While antibody responses in PLWH increased progressively after each vaccination, they were significantly reduced compared to the HIV-negative control group. This was particularly noteworthy for the Delta and Omicron variants. In contrast, CD4+ Th cell responses exhibited a vaccination-dependent increase, which was comparable in both groups. Interestingly, CD4+ T cell activation negatively correlated with the CD4 to CD8 ratio, indicating that low CD4+ T cell numbers do not necessarily interfere with cellular immune responses. Our data demonstrate that despite the lower CD4+ T cell counts SARS-CoV-2 vaccination results in potent cellular immune responses in PLWH. However, the reduced humoral response also provides strong evidence to consider PLWH as vulnerable group and suggests subsequent vaccinations being required to enhance their protection against COVID-19.